Applicability of 3-Dimensional Quantitative Coronary Angiography-Derived Computed Fractional Flow Reserve for Intermediate Coronary Stenosis - Enta, Kenji; Kataoka, Shohei; Kumagai, Asako; Kahata, Mitsuru; Yazaki, Kyoichiro; Inoue, Koji; Koganei, Hiroshi; Otsuka, Masato; Ishii, Yasuhiro (Circulation Journal, 2017)
Background:Quantitative flow ratio (QFR) is a newly developed image-based index for estimating fractional flow reserve (FFR).Methods and Results:We analyzed 151 coronary arteries with intermediate stenosis in 142 patients undergoing wire-based FFR measurement using dedicated software. Predefined contrast flow QFR, which was derived from 3-dimensional quantitative coronary angiography (3-D QCA) withThrombolysis in Myocardial Infarction (TIMI) frame counts, was compared with FFR as a reference. QFR had good correlation (r=0.80, P<0.0001) and agreement (mean difference: 0.01±0.05) with FFR. After applying the FFR cut-off ≤0.8, the overall accuracy rate of QFR ≤0.8 was 88.0%. On receiver operating characteristics analysis, the area under the curve was 0.93 for QFR. In contrast, 3-D QCA-derived anatomical indices had insufficient correlation with FFR and diagnostic performance compared with QFR.Conclusions:QFR had good correlation and agreement with FFR and high diagnostic performance in the evaluation of intermediate coronary stenosis, suggesting that QFR may be an alternative tool for estimating myocardial ischemia.